Olive Plant Treated with Different Geo-Material Foliar Film (Zeolite and Kaolin Based): Leaf Characteristics and Oil Quality - Annalisa Rotondi; Tommaso Ganino; Andrea Calderoni; Margherita Rodolfi; Rohini Dhenge; Lucia Morrone (Horticulturae)
Organic agriculture has few tools against pests and diseases and is constantly looking for effective and sustainable products such as geomaterials, i.e., zeolite. This study evaluates the physiological and morphological responses of olive plants (Olea europaea) to foliar applications of different geo-materials, specifically kaolin, natural zeolite, and ammonium-enriched zeolite. The research examines leaf anatomical modifications, including internal tissue structures, trichome and stomatal density, chlorophyll content, and gas exchange parameters, alongside the impact on fruit development and extra virgin olive oil (EVOO) quality. Results indicate that kaolin application negatively influenced transpiration and stomatal conductance, an effect corroborated by increased xylem vessel wall thickness. However, the reduction in stomatal conductance was attributed to a functional rather than morphological adaptation, as no significant changes in stomatal density or size were observed. Both geo-material treatments altered leaf surface properties, particularly peltate trichome characteristics. Notably, ammonium-enriched zeolite application enhanced photosynthetic rate during early olive development, likely due to its nutritional role, and contributed to increased fruit size and oil yield. These findings highlight the potential of geo-material-based foliar treatments as an effective strategy to optimize plant physiological performance and improve olive oil production in sustainable agricultural systems.